Apropriação dos recursos naturais e conflitos socioambientais no baixo São Francisco em Sergipe e Alagoas - Araújo, Sérgio Silva de (2016)
The population living in the low San Francisco in Sergipe and Alagoas are facing serious problems arising from the ownership of natural resources modes, promoted by the state, whose dams along the river channel are the biggest protagonists in the use of water resources. The electricity sector has appropriated the water and soil, generating environmental impacts that interfere in social practices, represented by the utilization of territories and resources available in the hydrographic basin. The general objective of the thesis is to analyze the model of appropriation of natural resources face the environmental impacts downstream of the Xingó Hydroelectric Plant. The specific objectives were: a) research and analyze the social, economic and environmental characteristics of the municipalities that compounds the low São Francisco area; b) identify, typify and analyse the socioenvironmental conflicts around rice production, production of small-scale fishing and the extinction of Ilha do Cabeço; c) analyze the environmental perception of the residents of the island of Cabeço/Brejo Grande/SE and; d) research and analyze the socio-environmental sustainability in low São Francisco and show the results through the Anthropogenic Impact Polygon drawn on radar chart. Anthropogenic activities resulting from the current ownership model in the country, under the generation of energy from hydroelectricity, introduces undesirable impacts on the natural environment. These impacts are perceived on the changes in water quality, soil, fauna, flora and hydrodynamics of rivers. Low San Francisco rive hosts this appropriation of resources model. This justifies the work, an interdisciplinary perspective analysis. The theoretical framework contributed with the necessary support for the analysis about the social processes that involve conflicts and among them, the unequal distribution of access and control over the resources of the natural environment. These foundations gave meaning to the path taken, the model of appropriation of natural resources generate environmental impacts, whose reflexes change social practices, the use of territories and resources, which in turn, introduces social and environmental conflicts. The object of study, the municipalities and the environment in the lower course of the river San Francisco, Xingó to its mouth, in Sergipe and Alagoas in 1990 period to 2010. The analysis method was qualitative-quantitative, descriptive exploratory with visits to the field to survey the environmental impacts, to make digital photographic records and interviews. The intention was to show the different uses of the resources of the watershed and the consequences that followed the construction of the Xingó dam. The social indicators related to extreme poverty, infant mortality and illiteracy rate; economic related to per capita income, culture of rice production, hand crafted fishing and; environmental related to the flow of the river, running water and inadequate sanitation. The actors interviewed in the survey are fishermen, farmers, members of the Basin Committee of the São Francisco and villagers from Cabeço. Environmental conflicts are around the resource control and are distributive, since they have unequal access. Around the impacts and space due to its length. Around the sacred or territorial because deterritorializes communities. Environmental perception of hill dwellers enmeshed tangible and intangible elements. It was concluded that the adjustment of the river flows affect the behavior of sustainability indexes, the production of rice, fishing, quality of life of coastal and the environment.